The Comprehensiveness of Strategic Decision Processes: Extension, Observations, Future Directions - Fredrickson, James W. (Academy of Management Journal, 1984)
A recent study in an industry with an unstable environment (Fredrickson & Mitchell, 1984) reported a negative relationship between comprehensiveness (a measure of rationality) and organization performance. An extension of that study establishes a positive relationship between comprehensiveness and performance in a stable environment.